Pengaruh Pengetahuan Investasi, Persepsi Return dan Persepsi Risiko Terhadap Minat Berinvestasi di Platform Bibit: Studi pada Mahasiswa UBP Karawang - Yuniar Maulidya; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out the influence of investment knowledge, perception of return and risk perception on the investment interest of students of Buana University of Karawang Struggle in the Plant Platform partially and simultaneously. The population includes the entire UBP Karawang student recorded on the 2023 forlap with a sample of 100 respondents, and the sample is calculated using the Slovin formula. Purposive sampling is used as a sampling technique. The Likert scale is used as a measurement scale on questionnaires in data collection. For instrument analysis, validity and reliability tests are used. The data analysis method applied is the double regression analysis, which is supported by the classical assumption test as well as the hypothesis test of the t test, the f test and the R2 test using the SPSS 26 program. This research results in whether investment knowledge, perception of return and risk perception significantly influence the investment interest of UBP Karawang students in the Bibit platform partially and simultaneously. Three free variables in this study influenced the interest of UBP Karawang students in investing in Bibit platforms (only 55,%) that means, many other free variable that can affect the interest investing UBP karawang students on Bibit Platform.